Analisis Motivasi dalam Rekrutmen Calon Anggota Panwaslu Kecamatan Pemilu Serentak Tahun 2024 - Muh. Aripin Nurmantoro (Jurnal Adhyasta Pemilu, 2022)
The concept of democracy that is applied to the 2024 simultaneous elections is expected to open up space for freedom of distribution of people's political rights in determining their choice, but in its implementation it takes the role of the Sub-district Panwaslu to oversee the implementation of the General Election in the Sub-district area because it is believed that the Election supervisor has a major contribution to the implementation of the General Election. Furthermore, the Subdistrict Panwaslu recruitment process in Indramayu Regency that has been carried out is a form of opening up public access to become election organizers where this is reflected in the representation of 686 registrants. This phenomenon becomes interesting to analyze in order to find out how high the motivation of candidates for the Sub-district Panwaslu members in Indramayu Regency for the upcoming simultaneous elections is, then a quantitative approach with a descriptive survey method is used, while closed questionnaires are used as an efficient and suitable data collection technique because the respondents are quite large and spread out. The results of the study have shown that motivation significantly has a positive influence in the process of registering candidates for members of the Sub-district Panwaslu, where confidence with a percentage of 86.49% is higher than other motivation indicators so that later this is expected to correlate with integrity and supervisory work in guarding democracy.